“Fé que pensa, razão que crê”: uma análise da relação entre as experiências religiosas e acadêmicas de estudantes de pedagogia da UEFS - Carneiro, Iane de Jesus (2023)
The present work aims to analyze how scientific knowledge and religious experiences of students on the Degree in Pedagogy of State University of Feira de Santana (UEFS) are related. It is theoretically based on theories about hybrid habitus and socialization, as well as studies on university youth and religiosity. It is theoretically based on theories about hybrid habitus and socialization, as well as studies on university youth and religiosity. The methodology articulates quantitative and qualitative techniques, involving the application of 89 questionnaires and 7 interviews with students on the Pedagogy course at UEFS producing data that were analyzed through descriptive statistical analysis and thematic categorization of the responses obtained from the statements. The search results showed that 84.2% of students are between 17 and 25 years old. Regarding ethnic and racial identification, 85.4% of students consider themselves black, of which 41% are brown and 43.8% are black. The predominance of two Christian religions was observed, with Protestants making up 31.5% of followers and Catholics making up 28.1%. Following what the studies by Scheliga, Knoblauch and Bellotti (2020) indicate, it was possible to observe that the Pedagogy course follows the scenario of the Brazilian religious field with the increase in the number of “without religion” or those without a religious identity and evangelicals/protestants. It is concluded that the religiosity of university students has a direct influence on their life trajectories, on their ways of seeing and understanding the world, on their academic life and on their professional training